International Students Attending Canadian Universities: Their Experiences with Housing, Finances, and Other Issues - Calder, Moira J.; Richter, Magdalena Solina; Mao, Yuping; Kovacs Burns, Katharina; Mogale, Ramadimetja Shirley; Danko, Margaret (Canadian Journal of Higher Education, 2016)
Universities recruit international students for a number of reasons, including enhancement of global contacts and reputation, to increase enrolment, and to generate revenue from tuition. These students face unique challenges as compared with domestic students, but no published studies or reports exist on this issue. In this article we report our findings from a survey and interviews with international graduate students, university personnel, and service providers assisting students. Students reported difficulties with finding affordable, adequate, and suitable housing; with finances, stemming from their ability to work or find employment, and from currency fluctuations; and with integration into a new university and an unfamiliar society. Administrators described limits to the assistance they could provide. Both groups suggested changes to address international students’ housing and financial issues. This study is part of a larger research project exploring housing and related issues among post-secondary students in a western Canadian city.